2022
DOI: 10.3390/molecules27206980
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Tocopherol Composition of Pomace and Seed Oil from Five Grape Varieties Southern Spain

Abstract: Grape pomace and seeds are important winemaking by-products. Their oils are rich in bioactive compounds such as fatty acids and tocopherols. We have characterized oils from both by-products from five Spanish grape varieties (Palomino Fino, Pedro Ximénez, Muscat of Alexandria, Tempranillo and Tintilla de Rota). A high content of UFAs was found in all the analyzed samples. Grape pomace oils generally had the same oleic acid (PUFAω-6) content as seed oils, and lower PUFA contents; they also had a markedly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Sherry comes in a range of styles, from the dry and light Fino, Amontillado and Oloroso, to the sweet and dark Pedro Ximénez [4,29]. Produced in the southern region of Andalusia, Malaga is made from several grape varieties, including Pedro Ximénez and Moscatel [30]. Malaga is a sweet fortified wine with flavours of raisins, caramel and honey.…”
Section: Spanish Fortified Winesmentioning
confidence: 99%
“…Sherry comes in a range of styles, from the dry and light Fino, Amontillado and Oloroso, to the sweet and dark Pedro Ximénez [4,29]. Produced in the southern region of Andalusia, Malaga is made from several grape varieties, including Pedro Ximénez and Moscatel [30]. Malaga is a sweet fortified wine with flavours of raisins, caramel and honey.…”
Section: Spanish Fortified Winesmentioning
confidence: 99%
“…Sherry comes in a range of styles, from the dry and light Fino, Amontillado, and Oloroso to the sweet and dark Pedro Ximénez [ 4 , 29 ]. Produced in the southern region of Andalusia, Málaga is made from several grape varieties, including Pedro Ximénez and Moscatel [ 30 ]. Málaga is a sweet and fortified wine with flavours of raisins, caramel, and honey.…”
Section: The Production Of Fortified Wines—patterns and Specificitiesmentioning
confidence: 99%
“…The results indicate that the oil's antioxidant properties can be used to slow down the oxidative changes of pork pâtés during storage. A study by Sallam et al [54] showed the antioxidant effect of black cumin oil at 1%, 2%, and 3% concentrations when used as an additive to beef patties. Furthermore, a study by Wojtasik-Kalinowska et al [25] showed that storage of raw minced pork at 4 ± 1 • C for eight days with an additive of 1.88% oil was as effective as using the synthetic antioxidant BHA.…”
Section: Tbarssmentioning
confidence: 99%